Innovative Strategy In Third Party Fund Management To Increase Liquidity In Indonesian Sharia Banks: Case Study Of BSI Kc Pematangsiantar Perintis - Mahira, Nazla Minda; Nurbaiti, Nurbaiti; Rahmani, Nur Ahmadi Bi (UNIVERSITAS PAKUAN, 2025)
This research aims to analyze innovative strategies for collecting Third Party Funds (DPK) to enhance liquidity at Bank Syariah Indonesia (BSI) KC Pematangsiantar Perintis. Using a qualitative approach and a case study method, this study explores various strategies, including incentive programs such as Pesta Hadiah and Rezeki Berkah, which have proven effective in attracting and retaining customer funds. Digitalization also plays a key role through the development of the BSI Mobile (BYOND) application, QRIS promotion, and the provision of EDC machines to support non-cash transactions. Additionally, the financial inclusion strategy through the expansion of the BSI Smart Agent (BSA) network has helped reach customers in remote areas. The findings indicate that the combination of incentive strategies, digital services, and financial inclusion positively contributes to deposit growth and liquidity stability. Despite challenges such as limited customer trust in digital systems and constraints in equipment procurement, these innovative approaches have strengthened BSI’s position in the Islamic banking industry. Therefore, this strategy can serve as a model for other Islamic banks in optimizing liquidity management and improving competitiveness within the Islamic financial sector.